Septic shock as a differential diagnosis of severe dengue fever in a child in Malaysia - a case report - Devaraj, Navin Kumar; Ragubathi, Mokshashri Naidu; Er, Sin Yee; Ching, Siew Mooi (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Dengue fever infection is common in many parts of the world and may result in serious complications such as dengue haemorrhagic fever, dengue shock syndrome, pleural effusion, pericardial effusion and multi-organ failure if not diagnosed early or treated adequately. This is more so in the so called susceptible group that includes children, pregnant mother, elderly patients, patients with heart, liver or kidney co-morbidity, obese patients as well as immunocompromised patient such as those with transplanted organs or human immune-deficiency infection. However in certain cases, severe dengue fever may mimic the presentation of septic shock which needs urgent and decisive management actions to be taken. This case report will look at a 7-year-old child who survived despite developing septic shock which was thought to be initially dengue fever with warning signs. Early referral and aggressive treatment in hospital prevented a direr consequence for this child.